An unusual progressive stridor. Issue 2 (June 2020) - Apraxine, Matveï; Mineur, Philippe; Huet, Jean; Beniuga, Gabriela; Colinet, Benoit
A 71-year-old man came to our pulmonary consultation with 6 weeks of progressive dyspnoea, hoarseness and, more recently, stridor. His past medical history included colorectal cancer treated with surgery and adjuvant chemotherapy, and type 2 diabetes mellitus. Prior to our consultation, his general practitioner had already ordered a chest computed tomography (CT) scan. The patient had undergone this CT scan 3 days before the consultation and it did not reveal any abnormalities. A flow–volume curve with a flattening of the inspiratory and expiratory limb suggests a proximal obstruction of the upper airways. Plasma cell neoplasms need to be considered in the differential diagnosis of an invasion of the upper respiratory tract. https://bit.ly/2K9lOXj